Experimental Studies on the Effect of Destructive Reagents on Metal Structural Elements - Chepkov, I.B.; Lapitsky, S.V.; Kuchinskiy, A.V.; Kuchinska, O.B.; Zirka, M.V.; Zvershkhovskiy, I.V.; Hurnovich, A.V.; Dokuchaev, O.V.; Andriyenko, A.M.; Oliarnik, B.O. (Powder metallurgy and metal ceramics, 2024)
Experimental studies were conducted to refine the theoretical provisions concerning the mechanism and kinetics of penetration for a metal melt consisting of destructive reagents, such as gallium, indium, tin, and zinc (destructive composition), along the grain boundaries in unstressed metal samples. It was experimentally confirmed that the penetration rate of the destructive composition was limited by processes at the liquid phase front, including dissolution of intergranular boundary areas, recrystallization to form solid solution crystals, and opening of new crack areas under the pressure of growing crystals. The experimental findings indicated a significant decrease in the strength of aluminum alloys resulting from the effect of the destructive composition. Analytical dependences and corresponding empirical coefficients characterizing the effects of the destructive composition on structural aluminum alloy elements under tensile loads were derived. These empirical coefficients enable the determination of conditions under which aluminum alloy structures fail under the influence of destructive compounds, considering the tensile stresses. The effect of the destructive alloy on the onset of fatigue damage and the durability of aluminum alloy structures under asymmetric cyclic stresses was examined. Significant reduction in the fatigue strength of aluminum structures under the influence of the destructive composition was experimentally confirmed.